Bases para o manejo de pragas de difícil controle em soja: eficiência de inseticidas para Helicoverpa armigera e efeito sistêmico de neonicotinóide sobre Euschistus heros - Kuss, Cassiano Carlos (2015)
The intensification of the attack of stink bugs and caterpillars on soybean are phytosanitary threats that concern various sectors of the soybean production chain, because of the difficulty of control as the damage potential that these present. From the 2012/2013 crop a new species of caterpillar, Helicoverpa armigera (Lepidoptera: Noctuidae), was detected in Brazil. To protect the crops of your attack the Ministry of Agriculture, Livestock and Food Supply (MAPA) authorized the emergency use of various insecticides molecules. Thus, a study was conducted to evaluate the performance of insecticides emergency basis allowed for H. armigera control in soybeans. In an experiment leaves obtained from treated plants in the field were provided to second and fourth instar larvae in the laboratory. In another spraying was performed on previously infested plants with second and third instar larvae in the field. Flubendiamide, clorantraniliprole, chlorfenapyr, indoxacarb and methoxyfenozide were insecticides with greater efficiency and control of H. armigera in laboratory experiment and biological insecticides, baculovírus (HzSNPV) and Bt (Bacillus thuringiensis var. Kurstaki HD-1), have intermediate mortality. In the experiment in flubendiamide field, spinosad, baculovírus and Bt showed satisfactory efficiency. The brown stink bug, Euschistus heros (Heteroptera: Pentatomidae), is the kind of bug more widely distributed in Brazil and which is more difficult to control. Neonicotinoid insecticides are one of the main groups of products used to control stink bugs and the study of their systemicity is of great importance for the foundation for the application of technology to optimize pest control and rationalize their use. Thus, a study was conducted to evaluate the effect of systemic insecticide thiamethoxam neonicotinoid in soybean plant on mortality of brown stink bug E. heros. Different strata of soybean plants grown in pots, were selectively sprayed and infested with E. heros adults to study the systemic effects of the product. The results indicate that there is upward translocation of thiamethoxam in soybean at R5.2, while in R6 was not observed systemic effect of this product on E. heros.